Expanding on Abraxane Safety: Temporal Insights and Future Directions for Adverse Event Analysis [Letter] - Yang F; Ge W (International Journal of Nanomedicine)
Fangcai Yang,1 Wukun Ge2 1Department of Clinical Nutrition, Ninghai First Hospital, Ningbo, Zhejiang, 315600, People’s Republic of China; 2Department of Clinical Pharmacy, Ninghai First Hospital, Ningbo, Zhejiang, 315600, People’s Republic of ChinaCorrespondence: Wukun Ge, Department of Pharmacy, Ninghai First Hospital, 142 Taoyuan Middle Road, Ningbo, Zhejiang, 315600, People’s Republic of China, Email notiong@alu.zcmu.edu.cn